"Liberal Arts are an Islamic Idea": Subjectivity Formation at Islamic Universities in The West*. Issue 1 (February 2016) - Sinclair, Kirstine
Abstract: The aim of this project is to discuss how Islamic universities in the West facilitate and condition the formation of modern Muslim subjectivities. The central question of the study is: How is the formation of modern forms of subjectivities tied together with the reinterpretation of Islamic traditions? The paper provides analysis of the curricula, and institution background, values and aims of two universities—Zaytuna College in Berkeley, California, the first Muslim liberal arts college in the U.S.; and Cambridge Muslim College, the first to offer a Diploma in Muslim community leadership in Britain. Alongside the textually founded analysis, interviews conducted with leadership, faculty and students, and participatory observation inform the discussion. Analysis demonstrates that both institutions see themselves as mediators between Islamic traditions and modern Muslims in the West, and as having a responsibility to engage in the development of both Muslim minorities and the wider societies within which they operate.